Abnormal developmental control of replication-timing domains in pediatric acute lymphoblastic leukemia - Ryba, Tyrone; Battaglia, Dana; Chang, Bill H.; Shirley, James W.; Buckley, Quinton; Pope, Benjamin D.; Devidas, Meenakshi; Druker, Brian J.; Gilbert, David M. (Genome Research, 2012)
Abnormal replication timing has been observed in cancer but no study has comprehensively evaluated this misregulation. We generated genome-wide replication-timing profiles for pediatric leukemias from 17 patients and three cell lines, as well as normal B and T cells. Nonleukemic EBV-transformed lymphoblastoid cell lines displayed highly stable replication-timing profiles that were more similar to normal T cells than to leukemias. Leukemias were more similar to each other than to B and T cells but were considerably more heterogeneous than nonleukemic controls. Some differences were patient specific, while others were found in all leukemic samples, potentially representing early epigenetic events. Differences encompassed large segments of chromosomes and included genes implicated in other types of cancer. Remarkably, differences that distinguished leukemias aligned in register to the boundaries of developmentally regulated replication-timing domains that distinguish normal cell types. Most changes did not coincide with copy-number variation or translocations. However, many of the changes that were associated with translocations in some leukemias were also shared between all leukemic samples independent of the genetic lesion, suggesting that they precede and possibly predispose chromosomes to the translocation. Altogether, our results identify sites of abnormal developmental control of DNA replication in cancer that reveal the significance of replication-timing boundaries to chromosome structure and function and support the replication domain model of replication-timing regulation. They also open new avenues of investigation into the chromosomal basis of cancer and provide a potential novel source of epigenetic cancer biomarkers.